The FeverApp registry – ecological momentary assessment (EMA) of fever management in families regarding conformity to up-to-date recommendations - David Martin; Jana Wachtmeister; Kai Ludwigs; Ekkehart Jenetzky (BMC Medical Informatics and Decision Making, 2020)
Abstract Background Fever is one of the most common symptoms of pediatric consultations and its mismanagement is a health care burden. Guidelines on fever management are incoherent and data on fever management are still missing. This study protocol describes an app-based registry to evaluate the fever management of parents. Objective The primary objectives are to assess guideline adherence (primary outcome) and parental confidence in managing fever, and thus to reduce overuse of antipyretics, antibiotics and healthcare providers. Secondary objectives include creating a “FeverApp” that will enable parents to handle fever safely and to use the FeverApp registry as symptom and fever management diary. Further objectives include developing and testing a symptom-led registry model by app-based acquisition of parental entries of febrile illness cycle data and developing and testing models of how an interactive app-based registry can enable nationwide EMA information to inform science, guideline and policy makers, and the public. Methods A FeverApp, guiding parents and carers in handling and documenting fever, will be developed with family pediatricians according to current guidelines and recommended for all parents in Germany. A registry will anonymously document features, management and outcomes of febrile episodes: basic sociodemographic and medical information, initial symptoms, course of fever, pharmacological and non-pharmacological interventions, consultations with doctors, outcomes, fever-associated fears, and app satisfaction. Results This app may improve communication quality and health, e.g. asthma and antimicrobial resistance. Results will be published via website www.feverapp.de . Trial registration This app-based registry protocol is registered in the German Clinical Trials Register (DRKS) with registration number: DRKS00016591 .